Geographic information systems, a tool for inventorying and managing urban land uses: The case of commercial uses - Anoun, Nourrdine; Hadjira, Lyesse (Journal of Architecture and environment of child, 2024)
Quantitative and qualitative changes, experienced by the trading system of Algerian cities, are the cause to think about organizing and planning their business structure, because the marketing function plays a crucial role in the organization and structuring of the area of the city. The purpose of this paper is the exploitation of the technical development of GIS in the management and monitoring of commercial occupations especially given the failure of said crude instruments. After this study we can report that the use of data from aerial photographs and field surveys allow the creation of a geographic information system able to produce digital plans updated and easy to save, operate and update. In addition it shows in detail the characteristics of different types of beneficiaries and commercial occupation is characterized by an interactive tool which makes a timely manner to various stakeholders for the organization or structuring of the business.